Integração de Dados JSON em Aplicações Ginga-NCL para Alerta de Pessoas Desaparecidas - Soares, Alice Lima; Moraes, Marcos Vinícios Mesquita de; Farias, Flávio Miranda de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Introduction: This paper explores the use of JSON for dynamic content management in interactive Digital TV applications developed with the Ginga-NCL middleware and NCLua scripting language Objective: The proposed application aims to simulate a missing persons alert system, inspired by the Amber Alert Brazil initiative. Methodology: The system’s architecture leverages Ginga-NCL’s modularity to facilitate maintenance and future scalability. Using JSON as the data format allows efficient, real-time updates of content, improving the responsiveness of the application. under the Brazilian standard. Results: The successful development of a functional prototype demonstrates the practicality of integrating JSONbased dynamic content in Digital TV applications, reinforcing its potential for public utility services